(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze and develop an educational quality management model in an effort to improve school accreditation at SD Negeri 158 Palembang. This research employed a qualitative approach using a descriptive method. The research subjects consisted of the principal, teachers, and educational staff selected through purposive sampling, in which respondents were chosen based on specific considerations related to their understanding of the implementation of educational quality management at the school. Data collection techniques included interviews, observations, and documentation. The collected data were analyzed through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the implementation of educational quality management in the school. The results of the study indicate that the implementation of educational quality management principles at SD Negeri 158 Palembang has been carried out through school program planning, effective learning process implementation, as well as continuous evaluation and improvement of various educational activities. In addition, several supporting factors in improving school accreditation were identified, such as effective principal leadership, teacher competence, and cooperation among school members. However, this study also found several inhibiting factors, including limited educational facilities and infrastructure as well as a lack of understanding regarding school accreditation administration management. This study is limited to one school setting; therefore, the findings cannot be generalized broadly. Future studies are recommended to involve more schools and develop more innovative and technology-based educational quality management models